Eksperimen Probabilitas Stopping Set pada Coded Random Access (CRA) Untuk Jaringan IoT - Nola Gabriella Hutapea; Yusnita Rahayu; Khoirul Anwar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
By increasing of users/devices number, Coded Random Access mechanism is suitable to enable successful access wireless successfully on super dense network. Problem of using Coded Random Access is stopping set appears. Stopping set is a harmful structure, where no other way for some trapped users in a set to be decoded. Stopping set is affected by degree distribution. This paper presents probability experiment of stopping set on Coded Random Access for Internet of Thing (IoT). It uses MATLAB R2016a as tool proving. The result of this research is used as performance networking prediction of future IoT. The results confirm that this research has a highly accuracy opportunity and becomes so practical. Then, a new graph stopping set is found on the result of simulation. The number of user/device randperm, ˄(x) and G affect the probability of stopping set on CRA for IoT network. More G approaches 1, the more number of stopping sets too appear and vice versa. For probability of stopping set on Coded Random Access, if G more keeps from 1, so occetence of stopping set on CRA prpbability is smaller. On the other side, if G gets closer to 1, so appearance of stopping set on CRA, probability is bigger.Keyword : Super Dense-Network, Coded Random Access, Stopping Set.